Rethinking Utopia: the search for 'topias' in the Paris catacombs. Issue 4 (1st October 2020) - Bingham, Kevin
ABSTRACT: Taking as its starting point the argument that obsession with Utopia has begun to decline, this paper considers what might replace the concept in the twenty-first century. The paper continues by drawing on the important work of Peter Sloterdijk and Tony Blackshaw to accentuate the point that the good life is less about following grand narratives than it is about inventing oneself through a process of self-creation that has been referred to as anthropotechnics . With this idea in mind, the paper goes on to unpack how a group of urban explorers find various substitutes for utopia in the subterranean space of the Paris catacombs, substitutes that deliver inimitable feelings of identity, togetherness and freedom. As it is argued, forms of leisure such as 'urbex' emerge as 'primary spheres' of anthropotechnics that instigate the formation of intertwining and interpenetrating 'topias' which have been referred to here as 'reterotopia', 'heterotopia' and 'scotopia'.